2018
DOI: 10.1097/sla.0000000000002954
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Status Biases Trauma-system Utilization and Appropriate Interfacility Transfer

Abstract: Insured patients with significant injuries initially evaluated at NTCs and level III/II TCs were less likely to be transferred. Such a finding appears to result in less optimal trauma care for better-insured patients and questions the success of transfer-guideline implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
2
13
1
Order By: Relevance
“…Insurance status has been shown to affect the transfer of pediatric trauma patients to higher levels of care 10,28 . In our study population, patients who were transferred to Level I PTCs were more likely to have a private insurance, but there was no difference among those with government insurance.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Insurance status has been shown to affect the transfer of pediatric trauma patients to higher levels of care 10,28 . In our study population, patients who were transferred to Level I PTCs were more likely to have a private insurance, but there was no difference among those with government insurance.…”
Section: Discussionmentioning
confidence: 72%
“…Insurance status has been shown to affect the transfer of pediatric trauma patients to higher levels of care. 10,28 In our study population, patients who were transferred to Level I PTCs were more likely to have a private insurance, but there was no difference among those with government insurance. However, after controlling for confounding factors, insurance status (insured vs. noninsured) was not statistically associated with the odds of mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Identifying what those factors are and attempting to disentangle them from the complex array of social determinants that lie at the heart of disparities is beyond the scope of this work, yet in looking at the other proposed mechanisms for insurance-based triage patterns, 14 a few interesting theories persist. We know from the results of this paper that insurance-based differences in the risk-adjusted odds of admission were lessened in rural settings located farther from larger trauma centers.…”
Section: Discussionmentioning
confidence: 99%
“…As such, they are an imperfect proxy of patient severity and a retroactive description of knowledge that, at the time of ED presentation, might not have been known. 14 Despite this, they remain the best methodology available to account for trauma severity in large databases 11 and provide a consistent definition with what has already widely been used. [11][12][13][14][15][16][17][18][19][20][21][22] Consistent with prior literature suggesting the potential emergence of a new form of insurance bias and potential inverse disparity favoring uninsured patients, [11][12][13][14][15][16][17][18][19][20][21][22] the results of this study found that adult patients with major injuries initially presenting to NTC EDs were less likely to be transferred if insured.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, hospitals are not required to transfer patients or potentially lose their Medicare funding (as would be the case if it were an EMTALA requirement), but they are instead incentivized to do so to avoid a malpractice suit. Thus, one research question is whether hospitals may inappropriately fail to transfer a patient for financial reasons (e.g., because they have Medicare or private insurance), even if they lack capability 108 , 137 . If research suggested that this was the case, policymakers could respond by affirmatively requiring hospitals to transfer patients if they lack capability.…”
Section: Regulatory Environmentmentioning
confidence: 99%